Crescimento e produção do feijoeiro comum cultivado sob déficit hídrico - Martins, Camila Aparecida da Silva (2013)
Water availability is one the main factors limiting the bean productivity. The objective of this study was to evaluate the effect of water deficit in the predawn leaf water potential, growth and yield of common bean cultivated in Oxisol and Ultisol.Two ex